Back Cover: Structure–Activity Relationships in Salinomycin: Cytotoxicity and Phenotype Selectivity of Semi‐synthetic Derivatives (Chem. Eur. J. 9/2017). Issue 9 (16th December 2016) - Borgström, Björn; Huang, Xiaoli; Hegardt, Cecilia; Oredsson, Stina; Strand, Daniel
Abstract : The ionophore salinomycin exerts selective activity against cancer stem cells. Synthetic strategies for modification of the directly accessible functional groups of this structure are explored, and a set of activity domains are identified by biological assays. Acylation of the C20 hydroxy group gives enhanced activity and selectivity against putative CSCs; disruption of ion coordinating motifs was not tolerated. The picture shows JIMT‐1 cells with 3D models of salinomycin approaching. More information can be found in the Full Paper by D. Strand et al. onpage 2077 ff.